The Relationship Between Self-Esteem And Body Image In Female College - Haris Munandar; Widya Shafa Nabilla (Suluh: Jurnal Bimbingan dan Konseling, 2023)
This study aims to examine the relationship between self-esteem and body image among female college students. The subjects in the study were 50 senior students who had completed their theses. Data were collected using a body image scale and a self-esteem scale. A Likert scale with four response alternatives was employed. The research data obtained were then analyzed using the Pearson Correlations product-moment correlation technique. The data analysis results indicate a very significant positive relationship between self-esteem and body image with a correlation coefficient (r) of 0.549 and a significance level (p) of 0.000. The conclusion of this study is that there is a very significant positive relationship between the self-esteem and body image of female college students. The higher the self-esteem of the students, the higher their body image, and conversely, the lower the self-esteem of the students, the lower their body image.